2006
DOI: 10.1074/jbc.m508165200
|View full text |Cite
|
Sign up to set email alerts
|

The RAP1 Guanine Nucleotide Exchange Factor Epac2 Couples Cyclic AMP and Ras Signals at the Plasma Membrane

Abstract: Epac-1 and -2 (exchange proteins directly activated by cyclic AMP) are guanine-nucleotide exchange factors for the GTPases Rap1 and -2. Epac2 but not Epac1 was found to possess a RA (Ras association) domain similar to that found in the Ras effector Ral-GDS. This domain specifically bound Ras-GTP, enabling oncogenic Ras to translocate Epac2 from the cytosol to the plasma membrane. Consequently, a small pool of plasma membrane-bound Rap1 was activated at the expense of bulk Rap1 located on intracellular organell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
90
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(94 citation statements)
references
References 66 publications
3
90
0
1
Order By: Relevance
“…A recent study by Scott and co-workers identified a complex linking Epac and Rap1 to A-kinase anchoring proteins in muscle cells, and the AKAP acted as a scaffold that bound other interacting signaling molecules such as PKA and cAMP phosphodiesterase (34). The localization of Epac2 can also influence its ability to activate specific pools of Rap1 (35). It is likely that the active Rap1 mutant does not interact as efficiently as wild type Rap1 with its normal targets.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Scott and co-workers identified a complex linking Epac and Rap1 to A-kinase anchoring proteins in muscle cells, and the AKAP acted as a scaffold that bound other interacting signaling molecules such as PKA and cAMP phosphodiesterase (34). The localization of Epac2 can also influence its ability to activate specific pools of Rap1 (35). It is likely that the active Rap1 mutant does not interact as efficiently as wild type Rap1 with its normal targets.…”
Section: Discussionmentioning
confidence: 99%
“…Conformational change of Epac1 induced by its binding to cAMP induces the translocation of Epac1 to the plasma membrane via the DEP domain [95]. Epac2A is localised [96,97]. The aminoterminal cAMP-binding domain A of Epac2A also mediates its localisation to the plasma membrane [93].…”
Section: Epac2a (Camp-gefii) As a Target Of Campmentioning
confidence: 99%
“…EP 3C ) and EP 4 mediate the PGE 2 -induced production of cAMP, which in turn activates Epac in addition to PKA. Epac then causes activation of PKCe via the Rap pathway, leading to sensitization of P2X3 receptors [9][10][11]16,35) (Fig. 1).…”
Section: )mentioning
confidence: 99%
“…EP 2 and EP 4 receptors are coupled to G s protein, and the agonist stimulation of those receptors activates adenylyl cyclase, which generates cyclic AMP (cAMP), followed by activation of protein kinase A (PKA) and, perhaps, exchange protein activated by cAMP (Epac). [8][9][10][11][12][13] 16) and may play roles in peripheral and/or spinal nociceptive processing. 8) 4.…”
Section: Microsomal Prostaglandin E Synthase-1 Asmentioning
confidence: 99%